The relationship between vitamin D level and disease activity and focal erosion in rheumatoid arthritis (Annals of Medical Research, 2021)
Aim: Bone loss,fragility,and fractures are well-described complications that affect quality of life, morbidity, and health care costs during the course of rheumatoid arthritis (RA). Besides its well-known role in bone metabolism, vitamin D is also an important immune modulator, meant to affect the disease activity of rheumatic disorders. However, conflicting results have been demonstrated about the relationship between levels of vitamin D and disease activity in RA. Primary aim of was to compare vitamin D levels and Bone Mineral Density (BMD) values between RA and control groups.The secondary aim was to assess the correlations between vitamin D and disease activity and radiologic damage in RA.Material and Methods: A total of 41 RA patients and 40 healthy controls were included in this study. The patient and control groups were between the ages of 18 and 65. Disease activity score 28 (DAS-28) was used to determine the severity of disease.Sharp/van der Heijde method was performed to evaluate the radiologic changes.Dual energy X-ray absorptiometry (DEXA) was performed to measure Bone Mineral Density (BMD).Enzyme-Linked Immunosorbent Assay (ELISA) method was used to measure serum D vitamin concentrations.Results: Vitamin D levels, the BMD-lumbar spine, BMD-femur total and BMD-femur neck values were significantly lower in the patient group (p = 0.012, p 0.001, p 0.001 and p 0.05). DAS-28 was significantly and negatively correlated with BMD values (p 0.05).Conclusion: Our study suggests that RA patients have lower vitamin D levels, BMD-lumbar spine, BMD-femur total and BMD-femur neck values. Higher disease activity increases bone loss in RA. Vitamin D levels and BMD values should be monitored for the risk of osteoporosis and fracture in RA.Keywords: Rheumatoid Arthritis; Vitamin D; Bone Mineral Density; Disease Activity; Radiologic Damage.
Keywords: Rheumatoid Arthritis; Vitamin D; Bone Mineral Density; Disease Activity; Radiologic Damage.